Current debates in urban theory: A critical assessment - Storper, Michael; J Scott, Allen (Geografares, 2018)
Urban studies today is marked by many active debates. In an earlier paper, we addressed some of these debates by proposing a foundational concept of urbanisation and urban form as a way of identifying a common language for urban research. In the present paper we provide a brief recapitulation of that framework. We then use this preliminary material as background to a critique of three currently influential versions of urban analysis, namely, postcolonial urban theory, assemblage theoretic approaches and planetary urbanism. We evaluate each of these versions in turn and find them seriously wanting as statements about urban realities.We criticise (a) postcolonial urban theory for its particularism and its insistence on the provincialisation of knowledge, (b) assemblage theoretic approaches for their indeterminacy and eclecticism and (c) planetary urbanism for its radical devaluation of the forces of agglomeration and nodality in urban-economic geography.
Keywords: agglomeration theory; assemblage theory; planetary urbanisation theory; post-colonial urbanism; urban theory